Evaluation of Piper betle mediated silver nanoparticle in post-harvest physiology in relation to vase life of cut spike of Gladiolus - Maity, T.R. (2021)
The synthesized Piper betle mediated silver nanoparticles (PbSNPs) were characterized by using UV-visible spectroscopy and transmission electron microscopy studies. It was revealed that PbSNPs ranges from 30 to 50 nm in diameter and spherical in shape. The experiments were conducted to study the effect of PbSNPs on post-harvest physiology, vascular blockage, prolonging vase life, and keeping the quality of cut spike of gladiolus. The treatment consisted of six vase solutions, viz. distilled water (control), 4% sucrose (T1), 4% sucrose + 100 ppm 5-SSA (T2), 4% sucrose + 2 ppm PbSNPs (T3), 4% sucrose + 4 ppm PbSNPs (T4), and 4% sucrose + 6 ppm PbSNPs (T5). Experimental outcomes depicted that T4 vase solution gives the best results in all the aspects statistically compared to its positive control (T2). The results also show PbSNPs in vase solution might have played a significant role for scavenging the reactive oxygen species by inducing antioxidant enzyme system at the time of senescence, leading to a decrease in lipid peroxidation and increase in the membrane stability.